2013
DOI: 10.4304/tpls.3.5.769-775
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exposure to the Visual Medium on Learning Pronunciation and Word Stress of L2 Learners

Abstract: Abstract-This study examined the effect of exposure to the visual medium on learning pronunciation and word stress. Thirty junior high school students participated in this study. They were divided into an experimental and a control group each included 15 students. The participants were given a pretest in order to make sure that they were homogeneous with regard to their pronunciation and word stress. Both groups received instruction on key to phonetic symbols available in the back of their textbooks and on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Thus, believing in suprasegmental features' outstanding role in communication, many scholars have discussed the ways in which they can be taught and learnt more effectively in classrooms(e.g. Brazil, Coulthard, & Johns, 1980;Fotovatnia & Omidi, 2013;Ladefoged, 2010;Roach, 2002). The results of these studies have shown direct relationship between suprasegmental features learning and different variables such as attitudes towards L1 and L2.…”
mentioning
confidence: 99%
“…Thus, believing in suprasegmental features' outstanding role in communication, many scholars have discussed the ways in which they can be taught and learnt more effectively in classrooms(e.g. Brazil, Coulthard, & Johns, 1980;Fotovatnia & Omidi, 2013;Ladefoged, 2010;Roach, 2002). The results of these studies have shown direct relationship between suprasegmental features learning and different variables such as attitudes towards L1 and L2.…”
mentioning
confidence: 99%